Looking back and going forward in IT - Corniou, Jean-Pierre (ISTE., 2006)
Information technology now possesses an all-pervading influence in society: all areas of the social and corporate worlds use IT. However, despite its integral importance in society today, its development and future is often overlooked. This book places IT in perspective by tracing its development through time, covering its origins in business, the massive expansion of the role of IT at the end of the 20th century, the growth of the internet, and the successes and failures of companies involved in this development. Despite its ubiquity in the modern world, the author highlights that efficient us.